2022
DOI: 10.1002/trc2.12301
|View full text |Cite
|
Sign up to set email alerts
|

A pragmatic dementia risk score for patients with mild cognitive impairment in a memory clinic population: Development and validation of a dementia risk score using routinely collected data

Abstract: Introduction This study aimed to develop and validate a 3‐year dementia risk score in individuals with mild cognitive impairment (MCI) based on variables collected in routine clinical care. Methods The prediction score was trained and developed using data from the National Alzheimer's Coordinating Center (NACC). Selection criteria included aged 55 years and older with MCI. Cox models were validated externally using two independent cohorts from the Prospective Registry o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…However, the generated SVM models performed the best, with an accuracy of 93.3% for all patients, 94.4% for men exclusively, and 95.5% for women-only models. The top 10 significant predictors based on the developed SVM model for all patients are ranked as ( Winblad et al, 2016 ) education, ( Cummings-Vaughn et al, 2014 ) bedtime, ( Ferencz and Gerritsen, 2015 ) taking pills for chronic pain, ( Wang et al, 2022 ) diabetes, ( Wang et al, 2021 ) stroke, ( Doblhammer et al, 2022 ) gender, ( Goerdten et al, 2019 ) chronic pains, ( Kilander et al, 1998 ) coronary artery diseases, and ( Walker et al, 2017 ) wake-up time. The key novelty of this study is the early detection of cognitive function without relying on the radiological findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the generated SVM models performed the best, with an accuracy of 93.3% for all patients, 94.4% for men exclusively, and 95.5% for women-only models. The top 10 significant predictors based on the developed SVM model for all patients are ranked as ( Winblad et al, 2016 ) education, ( Cummings-Vaughn et al, 2014 ) bedtime, ( Ferencz and Gerritsen, 2015 ) taking pills for chronic pain, ( Wang et al, 2022 ) diabetes, ( Wang et al, 2021 ) stroke, ( Doblhammer et al, 2022 ) gender, ( Goerdten et al, 2019 ) chronic pains, ( Kilander et al, 1998 ) coronary artery diseases, and ( Walker et al, 2017 ) wake-up time. The key novelty of this study is the early detection of cognitive function without relying on the radiological findings.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, each table row demonstrates an observed class, and each column is a predicted class. Several statistical methods of performance evaluation were used for assessing the established models, including prediction accuracy, recall (true positive rate), precision (positive predictive value), and F1 score, as described in Equation (1 – 4) ( Wang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important finding from this elicitation study is that some but not all predictors identified as important for dementia risk prediction in the research literature are being routinely collected or analyzed in clinical practice, existing registries, and observational studies. Age, which was identified as the most important predictor by the expert panel, is an example of a variable routinely collected and included as a predictor in many dementia risk‐scoring algorithms 5,20,21 but not all 22 . In contrast, APOE4 status, which is commonly included in published risk scores, 5 is not routinely collected in clinical practice and was only ranked 20th by the experts.…”
Section: Discussionmentioning
confidence: 99%
“…Another framework based on a multifactorial cascade model of disease progression was used to simulate a personalized response to anti-amyloid therapies using either aducanumab or donanemab 119. The model simulated both short-(78 weeks) and long-term (10 years) individualized responses that took into account potential side effects such as amyloid-related imaging abnormalities (ARIA).A dementia risk score, the Mild Cognitive Impairment to Dementia Risk (CIDER) score, designed to be used in primary care to predict time to all-cause dementia within 3 years of an MCI diagnosis, was developed in the NACC cohort and validated in two cohorts including ADNI 120. CIDER was implemented as a nomogram with variables easily determined in clinic: age, sex, education, marital status, hypertension, mood disorder, and either MoCA or MMSE (FigureS16in supporting information).…”
mentioning
confidence: 99%